Seismic Hazards and Construction Vibrations - Moderie, Justin; Rippe, Arlan H (Contemporary Topics in Deep Foundations, 2009)
Redevelopment of an area along the waterfront in Portland, Oregon presented many geotechnical design and construction challenges for a 16-story building. Saturated river sediments and old industrial fills were susceptible to liquefaction and required seismic hazard mitigation, deep foundations, ground improvement, construction near sensitive structures, and a basement below groundwater. Many of these challenges on this 0.4-hectare (1-acre) site currently are being researched, and consequently are often subject to differing engineering judgment and analysis rationale. Design and constructability of the foundation elements of this 16-story building present a case worthy of study. Three important questions resolved during the project include: 1) Will installation of stone columns densify lithified deposits of non-plastic silt and sand? 2) What is the magnitude of vibration at varying distances from pile driving and from installation of stone columns, near a historic, active, fragile composite concrete and brick storm sewer pipe? 3) Will pile driving and installation of stone columns cause liquefaction of nearby soils supporting the storm sewer pipe? These questions were answered during construction. Pre and post-construction CPT testing, vibration monitoring, survey markers, and video monitoring of the storm sewer were used. Data collected provide supportive proof of the approaches, research, and rationale.